Code-Switching as A Strategy of Diasporic Identity Articulation in American as Paneer Pie - Purnawati, Ariza; Manneke Budiman; Suma Riella Rusdiarti (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study examines the phenomenon of code-switching as a strategy for articulating diasporic identity in the children's novel entitled American as Paneer Pie. Using a qualitative method, this analysis applies Gumperz' concept of code-switching and Stuart Hall's articulation of identity to examine how code-switching in the narrative not only represents language switching but also articulates cultural identity in the context of diaspora. The results show that out of 38 data points 34 use metaphorical code-switching in the form of Indian food, tradition, and cultural terms to emphasize Lekha's attachment to her cultural roots and show her identity negotiation process in the American multicultural environment. The other four data use situational code-switching to indicate specific social interactions, such as when Lekha spoke with her family or when she responded to Hindi with English. The articulation of diaspora identity in this novel is realized through the practice of code-switching, which is used as a form of diaspora negotiation between language and culture.